PENGGUNAAN IMPLAN GIGI SEBAGAI ALTERNATIF GIGI TIRUAN - Stephani Dwiyanti; Mora Octavia (Bahasa Indonesia, 2019)
Introduction: Loss of teeth leads to many problems anatomically and physiologically, leading to nutritional intake disturbances, and even affect patient’s psychological condition. There are several alternatives for tooth replacement such as removable denture, fixed partial denture (bridge), and implant. This case report described a loss of a single molar and its replacement with implant.Case Report: A 36-year-old female patient came with a chief complaint of missing lower left posterior teeth 5 years ago due to big caries. Patient wanted to replace with implant. Comprehensive evaluation was done to make sure that she was indicated for dental implant. Insertion of megagen implant was done on the first phase of surgery. Implant was left for 3 months for osseointegration. Insertion of healing abutment was done on the second phase of surgery and was left for 1 week. Impression was done and a screw-retained metal porcelain crown was made for the implant.Conclusion: Rehabilitation of tooth loss with implant requires several steps which are time-consuming and expensive. However, many patients still opt for implant therapy. Compared to other alternative therapy, implant is the most comfortable form of denture, does not damage adjacent teeth, has a high survival rate, and are more cost-effective in the long run.